The Clinical Utility of D-Dimer and Prothrombin Fragment (F1+2) for Peripheral Artery Disease: A Prospective Study - Sara Arfan; Abdelrahman Zamzam; Muzammil H. Syed; Shubha Jain; Niousha Jahanpour; Rawand Abdin; Mohammad Qadura (Biomedicines, 2022)
D-dimer and prothrombin fragment (F1+2) levels are elevated in patients with peripheral artery disease (PAD). We examined their prognostic potential in predicting decreasing ABI and major adverse limb events (MALE). A total of 206 patients were recruited from St. Michael’s Hospital and followed for two years. Baseline plasma concentrations of D-dimer and F1+2 were recorded. Pearson’s correlation was used to assess the correlation between the biomarkers and ABI at year 2. During follow-up, multivariable Cox proportional hazard analysis was performed to investigate their role in predicting decreasing ABI (defined as change in ABI > −0.15) and MALE (defined as the need for arterial intervention or major limb amputation). Cumulative survival was assessed using Kaplan–Meier analysis. Baseline D-dimer and F1+2 levels were elevated in PAD patients (median (IQR) 1.34 (0.80–2.20) for D-dimer and 3.60 (2.30–4.74) for F1+2; p = 0.001) compared to non-PAD controls (median (IQR) 0.69 (0.29–1.20) for D-dimer and 1.84 (1.17–3.09) for F1+2; p = 0.001). Both markers were negatively correlated with ABI at year 2 (r = −0.231 for D-dimer, r = −0.49 for F1+2; p = 0.001). Cox analysis demonstrated F1+2 and D-dimer to be independent predictors of PAD status (HR = 1.27, 95% CI = 1.15–1.54; p = 0.013 for D-dimer and HR = 1.28, 95% CI = 1.14–1.58; p = 0.019 for F1+2). Elevated baseline concentrations of D-dimer and F1+2 were associated with high incidence of decreasing ABI and 1- and 2-year event-free survival (62% and 86%, respectively). Combined analysis of D-dimer and F1+2 provides important prognostic information that facilitates risk stratification for future disease progression and MALE outcomes in patients with PAD.